2011
DOI: 10.3109/13880209.2011.568623
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and cytotoxic activity of polyphenolic compounds isolated from the leaves ofLeucenia leucocephala

Abstract: These findings demonstrate that the leaves of L. leucocephala contain a considerable amount of polyphenolic compounds with high antioxidant properties, thus it has great potential as a source for natural health products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 35 publications
2
14
1
Order By: Relevance
“…From the point of controlling the side effects of chemical drugs used in the treatment of cancer, seeking drugs of natural origin becomes mandatory. Hepatocellular carcinoma (HepG2) cells represent one of the most widely used experimental models for in vitro studies on liver cancer (Haggag et al, 2011). Our results are in accordance with previous results on cytotoxic activity of entomopathogenic fungi; Zhang et al (2004) demonstrated that the cytotoxic activity of ethyl acetate extracts of Cordyceps sinensis on human leukemia cell line was high.…”
Section: Discussionsupporting
confidence: 91%
“…From the point of controlling the side effects of chemical drugs used in the treatment of cancer, seeking drugs of natural origin becomes mandatory. Hepatocellular carcinoma (HepG2) cells represent one of the most widely used experimental models for in vitro studies on liver cancer (Haggag et al, 2011). Our results are in accordance with previous results on cytotoxic activity of entomopathogenic fungi; Zhang et al (2004) demonstrated that the cytotoxic activity of ethyl acetate extracts of Cordyceps sinensis on human leukemia cell line was high.…”
Section: Discussionsupporting
confidence: 91%
“…The results were in coordination with antimicrobial effect of WMRE as indicated by zone of inhibition in the present study. Haggag et al (2011) and Mushtaq et al (2015) also attributed antibacterial activity of WMRE to high phenolic compounds (110.85 ± 8.85 mg GAE/g of freshWRM extracts).…”
Section: Microbial Qualitymentioning
confidence: 97%
“…Awareness regarding the cumulative biological characteristics of phenolics, including anti-inflammatory, antibacterial, vasodilatory actions, anticarcinogenic, antiviral, antithrombotic, antiallergic, and hepatoprotective effects (Del Bano et al 2006;Jayaram and Dharmesh 2011;Turner et al 2005), have led to the extensive study of the bioactivities of these plant materials (Haggag et al 2011). During the present study, plant cell walls were enzymatically treated by cellulasic, pectinase, and hydrolytic enzymes (acid cellulase), which ultimately improved the liberation of glycosidically entrapped phenolic compounds.…”
Section: Phenolic Compounds In Clpmentioning
confidence: 99%